Penurunan BOD5 dan COD pada Air Permukaan Pasar Umum Negara dengan Metode Filtrasi Sederhana - Septi Ika Nurfadila; Okik Hendriyanto Cahyonugroho (INSOLOGI: Jurnal Sains dan Teknologi, 2023)
The surface water of the Mertasari River (upstream) in Jembrana Regency, Bali is polluted with waste water due to the activities of the Negara Public Market (PUN). So that the quality of surface water decreases which is characterized by increasing levels of pollutant parameters. This study aims to determine the effectiveness of simple filtration tests with variations in the arrangement of filter media to reduce BOD5 and COD that exceed quality standards. The research method uses purposive sampling to determine the sampling location. From the results of water quality, the values of 8 mg/L and 29 mg/L respectively were obtained, which did not meet the quality standards based on Government Regulation of the Republic of Indonesia No. 22 of 2021. The arrangement used for filter media consists of palm fiber, sand, gravel, activated carbon, and zeolite. The filtration test treatment was carried out with three sampling times for each parameter with the amount of removal obtained BOD5 by 93.75% and COD by 96.14%. From these results, the final value of the BOD5 parameter is 0.9 mg/L and COD is 1.12 mg/L. So from the test results, simple filtration with the specified media arrangement is considered effective in reducing BOD5 and COD pollutant levels in surface water bodies around the State Public Market.